Structure and dielectric properties at phase transition of Na1/2Bi1/2TiO3-BaTiO3 solid solutions. (8th August 2016) - Plaude, A.; Ignatans, R.; Birks, E.; Dunce, M.; Antonova, M.; Sternberg, A.
ABSTRACT: Phase coexistence region is studied by x-ray diffraction for Na1/2 Bi1/2 TiO3 -BaTiO3 solid solutions in the tetragonal phase side from the morphotropic phase boundary. The first order ferroelectric phase transition, determined from a jump in the temperature dependence of dielectric permittivity, is located inside the coexistence region of cubic and tetragonal phases and is below the temperature, where tetragonality disappears. At low BaTiO3 concentrations phase transition into ferroelectric state at cooling is slowly approached in time and is smeared over large temperature range. Rietveld method, applied for more precise evaluation of phase content, reveals large local deformations inside the ferroelectric phase.